Zidni story: thank you Grandma Siti - Toha @ Tohara, Abdul Jalii; Nazir, Faridah; Ramdzan Ali, Al Amirul Eimer (Kulliyyah of Languages and Management, 2023)
Zidni Story Thank You Grandma Siti is one of the titles from the series of children's activity and coloring books through the Zidni Story label. This activity and coloring book contains a short story about a girl named Zidni. This book contains 12 pages of story text with black and white sketches that children can color. Next, this book also has four pages with language game activities.